Conflict and Catastrophe Medicine A Practical Guide - Ryan, James; Mahoney, Peter F.; Greaves, Ian; Bowyer, Gavin (Springer London, 2002)
Conflict and Catastrophe Medicine - A Practical Guide provides a framework for use by health professionals visiting a resource-constrained environment. Encompassing problems brought about by local conflict or natural disasters, the book covers preparation, organisation, logistics, treatment of major trauma and medical emergencies, and the special problems of delivering medicine in a hostile environment. Conflict and Catastrophe Medicine - A Practical Guide comprehensively tackles: - self-preparation of health professionals to face a range of medical and related problems which occur in hostile and remote environments; - war and disaster medicine, covering acute management, rehabilitation, reconstruction and prevention; - bridging the fields of medicine, nursing, international relations, history, politics and economics. The book also touches on nutrition, infection, trauma, psychiatry and psychological medicine and training. James Ryan, Leonard Cheshire Professor of Conflict Recovery, Royal Free and University College Medical School, London, UK Peter F Mahoney, Consultant Anaesthetist and Honorary Senior Lecturer in Conflict Medicine, Leonard Cheshire Centre, Royal Free and University College Medical School, London, UK Ian Greaves, Lecturer in Conflict Medicine, Leonard Cheshire Centre, Royal Free and University College Medical School, London, UK Gavin Bowyer, Consultant in Orthopaedic Surgery, Southampton General Hospital, UK.
Keywords: Emergency Medicine; Traumatic Surgery; Surgical Orthopedics; Intensive / Critical Care Medicine; Nursing; Emergency medicine; Trauma; Orthopedic surgery; Critical care medicine; Katastrophenmedizin; Aufsatzsammlung